Analisis Dampak Pembangunan Berkelanjutan Terhadap Lingkungan di Kawasan Industri Cikarang, Kabupaten Bekasi - Nur Utomo (Madani Connection, 2025)
Cikarang, a major industrial hub in Bekasi Regency, Indonesia, faces significant challenges in achieving sustainable development despite its economic growth. This study evaluates the environmental, social, and economic impacts of industrial development in Cikarang, aiming to provide recommendations for sustainable practices. The region contributes significantly to West Java's GDP, with the automotive and electronics sectors as key drivers. However, industrial activities have led to environmental degradation, including air and water pollution, often exceeding WHO standards. The study highlights the importance of responsible natural resource management and the need for companies to comply with environmental regulations. Socially, industrial development has created employment opportunities but also caused issues like migration and strain on local infrastructure. A qualitative descriptive approach is used, referencing relevant sources to analyze these impacts.Key challenges include a lack of awareness and commitment to environmental practices among industries, as well as the need for improved stakeholder collaboration. The implementation of appropriate technology, such as real-time environmental monitoring systems, is crucial. However, this is hampered by insufficient human resource skills and inadequate technological infrastructure. Addressing these challenges requires strategies such as enhancing human resource capacity, strengthening digital infrastructure, implementing data-driven governance, fostering stakeholder collaboration, and raising environmental awareness. These measures are essential to ensure that Cikarang's industrial development is both economically beneficial and environmentally sustainable.